Экстраполяционно-геометрический метод определени насыпной плотности порошков сверхтвердых материалов - Петасюк, Г.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
New method of determination of packed density of superhard material powders has been presented. The method is based on 3D-simulation methodology with applying of affinity space mapping mathematics. The results of this method approbation to standard powders of synthetic diamond and cubic boron nitride are given.